Primary School Head teachers’ Perceptions of Competencies gained from Training at Kenya Education Management Institute Training in Uasin Gishu County, Kenya - Ongori , Josephine; Kitainge , Kisilu; Kipkoech , Lydia (African Journal of Education,Science and Technology (AJEST), 2018)
The management of primary schools in every country in the world calls for head teachers to be well trained and qualified to discharge school duties. Due to enormous resources and effort that is used in training, managers are under pressure to demonstrate the effectiveness of training. Despite the introduction of Diploma in Education Management by Kenya Education Management Institute Training (KEMI) in 2011, there are numerous cases of mismanagement reported in some schools in Uasin Gishu County. This paper sought to assess primary school headteachers’ perceptions of competencies gained from KEMI in Uasin Gishu County, Kenya. The study utilised descriptive research design and was guided by Kolb’ Experiential Learning Cycle theory. The study targeted 471 headteachers, 5 sub-county education officers and one county education officer. Simple random sampling was used to select 30 % (141) of the public primary schools in the county. All headteachers, 5 sub-county education officers and the county education officer were purposively selected. Data was collected using a questionnaire and an interview schedule. Quantitative data collected was analysed descriptively while the qualitative data was presented thematically. The findings were presented in frequency tables, pie charts and histograms. The study established that majority of the headteachers had a negative perception towards KEMI training in relation to their management competencies. The headteachers consider management training as a mere routine and they only attend training to secure their jobs. The study recommends that the training period should be extended to enable headteachers cover adequately the management skills as indicated in the KEMI Diploma curriculum.